The Social Consequences of the Deportation of Polish Citizens Deep into the USSR in 1940–1941 - Głowacki, Albin (Faces of War, 2024)
As a result of four mass deportations carried out by the NKVD officers in 1940–1941, over 320,000 Polish citizens were deported into the USSR from the eastern territories of the Republic of Poland annexed by Moscow (according to NKVD sources). They were considered to be the most dangerous to the communist regime. At that time, families of military men, foresters, those arrested or held in prisoner-of-war camps, and war refugees (mainly Jews) who refused to accept USSR citizenship, as well as the families of participants in the ‘counter-revolutionary Ukrainian and Polish nationalist organisations’ were resettled in cattle railway cars. The journey to exile lasted 2–4 weeks. People were settled in the northern regions of the European part of Russia, in the Urals, Siberia, and Kazakhstan. There, they performed very hard physical work in the logging of forests, in mines, agriculture, and construction – in a harsh climate, without training, without knowledge of the local language, without the right tools, without holidays, and without proper medical care and medicine. They commonly lacked food, workwear, shoes, and hygiene products. They lived in primitive barracks, in ruined farm buildings, in pit-houses, or rented mediocre accommodations from the locals. The constant struggle for survival taught them cunning, theft, and accelerated their acquisition of various professional qualifications. They had to adjust to life in extreme poverty, knowing that they could not break down or give in to doubt. The living conditions encouraged the development of various diseases and resulted in accelerated mortality. The exiles rarely decided to marry or expand their families, which increased demographic losses. The most common and lasting effects of the stay in exile concern the mental and physical condition of the victims of deportation. Their psyches were dominated by anxiety, fear, inferiority complex, and hostility. They feared war, hunger, inhumane living conditions, terror, and violence. Frequently, only religion gave them some consolation and helped them survive. Yet, the dramatic fate of living in exile cemented family ties, and mothers became the main characters. The children grew up prematurely and hardened themselves,mastering the rigid rules of life early. Since they did not have the opportunity to learn at school, their academic development was limited, if any, and they did not pursue its amendment even when they returned to their homeland. After the war, not all exiles returned to Poland – many lie in nameless graves in Siberia and Central Asia. Some Polish citizens (Ukrainians, Belarusians, Russians, Lithuanians) were denied the right to repatriation in 1945. In many cases, those who left the USSR in 1942 with General W. Anders’s Polish Army chose life in the free world of the West. From the depths of the USSR, people returned physically and mentally exhausted, sometimes as invalids. In the material sense, they had nothing, as their pre-war property was lost to the Soviets. In exile, they strengthened their love for their homeland and appreciated its existence. At the same time, they learned the realities of the socialist system, which they not only hated but also strongly rejected.